The Role for Virtual Patients in the Future of Medical Education. (September 2016) - Berman, Norman B.; Durning, Steven J.; Fischer, Martin R.; Huwendiek, Soren; Triola, Marc M.
Abstract : The medical education community is working—across disciplines and across the continuum—to address the current challenges facing the medical education system and to implement strategies to improve educational outcomes. Educational technology offers the promise of addressing these important challenges in ways not previously possible. The authors propose a role for virtual patients (VPs), which they define as multimedia, screen-based interactive patient scenarios. They believe VPs offer capabilities and benefits particularly well suited to addressing the challenges facing medical education. Well-designed, interactive VP-based learning activities can promote the deep learning that is needed to handle the rapid growth in medical knowledge. Clinically oriented learning from VPs can capture intrinsic motivation and promote mastery learning. VPs can also enhance trainees' application of foundational knowledge to promote the development of clinical reasoning, the foundation of medical practice. Although not the entire solution, VPs can support competency-based education. The data created by the use of VPs can serve as the basis for multi-institutional research that will enable the medical education community both to better understand the effectiveness of educational interventions and to measure progress toward an improved system of medical education.